Graphical Gaussian process regression model for aqueous solvation free energy prediction of organic molecules in redox flow batteries. Issue 43 (1st November 2021) - Gao, Peiyuan; Yang, Xiu; Tang, Yu-Hang; Zheng, Muqing; Andersen, Amity; Murugesan, Vijayakumar; Hollas, Aaron; Wang, Wei
Abstract : Machine learning model pipeline for solvation free energy prediction of organic molecules. Abstract : The solvation free energy of organic molecules is a critical parameter in determining emergent properties such as solubility, liquid-phase equilibrium constants, p K a and redox potentials in an organic redox flow battery. In this work, we present a machine learning (ML) model that can learn and predict the aqueous solvation free energy of an organic molecule using the Gaussian process regression method based on a new molecular graph kernel. To investigate the performance of the ML model for electrostatic interaction, the nonpolar interaction contribution of the solvent and the conformational entropy of the solute in the solvation free energy, three data sets with implicit or explicit water solvent models, and contribution of the conformational entropy of the solute are tested. We demonstrate that our ML model can predict the solvation free energy of molecules at chemical accuracy with a mean absolute error of less than 1 kcal mol −1 for subsets of the QM9 dataset and the Freesolv database. To solve the general data scarcity problem for a graph-based ML model, we propose a dimension reduction algorithm based on the distance between molecular graphs, which can be used to examine the diversity of the molecular data set. It provides a promising way to build a minimum training set to improve prediction for certain test sets where the space of molecular structures is predetermined.